2010
DOI: 10.1007/s00381-010-1130-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy in previously shunted children: a retrospective study

Abstract: In our experience, ETV secondary to shunt malfunction in pediatric patients has a success rate of 64%. As it is a safe and rapid treatment option even in emergency conditions, it is worth performing this procedure in previously shunted children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
36
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 23 publications
7
36
2
Order By: Relevance
“…This definition is supported by Bilginer et al [86] and Marton et al [87]. In our series we also observed that 28 of the 34 patients with previous VPSs were children.…”
Section: Discussionsupporting
confidence: 89%
“…This definition is supported by Bilginer et al [86] and Marton et al [87]. In our series we also observed that 28 of the 34 patients with previous VPSs were children.…”
Section: Discussionsupporting
confidence: 89%
“…Patient age and the etiology of hydrocephalus have been reported to be associated with outcomes after ETV 4,5,7,20,22,23,25,26,30) . Interestingly, the results are different when ETV is performed after shunt failure (secondary ETV) than when ETV is performed as an initial treatment modality for hydrocephalus (primary ETV).…”
mentioning
confidence: 99%
“…Primary and secondary ETV outcomes for post-hemorrhagic hydrocephalus are 27% and 71%, respectively, and for post-meningitic hydrocephalus they are 0% and 75%, respectively 23) . Recently, Marton et al 22) reported outcomes of secondary ETV in pediatric patients and described a post-operative protocol. In this paper, we present our data from a retrospective study of secondary ETV, and we propose a simple and reasonable post-operative protocol that can detect ETV failure.…”
mentioning
confidence: 99%
“…Marton et al concluded that "ETV secondary to shunt malfunction in pediatric patients has a success rate of 64%. As it is a safe and rapid treatment option even in emergency conditions, it is worth performing this procedure in previously shunted children [1]." Indeed, a similar report on the success rate of ETV was recently reported by O'Brien et al [2].…”
mentioning
confidence: 70%
“…
Dear EditorEditor, I read the recent publication on endoscopic third ventriculostomy (EVT) by Marton et al with a great interest [1]. Marton et al concluded that "ETV secondary to shunt malfunction in pediatric patients has a success rate of 64%.
…”
mentioning
confidence: 99%